2015
DOI: 10.1038/srep14754
|View full text |Cite
|
Sign up to set email alerts
|

Increasing prevalence of ciprofloxacin-resistant food-borne Salmonella strains harboring multiple PMQR elements but not target gene mutations

Abstract: Fluoroquinolone resistance in Salmonella has become increasingly prevalent in recent years. To probe the molecular basis of this phenomenon, the genetic and phenotypic features of fluoroquinolone resistant Salmonella strains isolated from food samples were characterized. Among the 82 Salmonella strains tested, resistance rate of the three front line antibiotics of ceftriaxone, ciprofloxacin and azithromycin was 10%, 39% and 25% respectively, which is significantly higher than that reported in other countries. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
92
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(106 citation statements)
references
References 37 publications
12
92
2
Order By: Relevance
“…), our finding of an in vitro susceptibility above 90% for these antibiotics (except NAL) indicates still an acceptable effectiveness, however, is very likely that the percentage of AMR could increase steadily due to mobile genetic elements like plasmids, transposons or integrons and subsequently their dissemination through animal‐origin food, this scenario is observed in other countries, especially from Asia, where S. enterica isolates from pork and chicken meat have a higher resistant rate for all the antibiotic tested in comparison with our work (up to 39% for CIP, 10% for CTX and 40% for GEN) (Lin et al . ).…”
Section: Discussionmentioning
confidence: 97%
“…), our finding of an in vitro susceptibility above 90% for these antibiotics (except NAL) indicates still an acceptable effectiveness, however, is very likely that the percentage of AMR could increase steadily due to mobile genetic elements like plasmids, transposons or integrons and subsequently their dissemination through animal‐origin food, this scenario is observed in other countries, especially from Asia, where S. enterica isolates from pork and chicken meat have a higher resistant rate for all the antibiotic tested in comparison with our work (up to 39% for CIP, 10% for CTX and 40% for GEN) (Lin et al . ).…”
Section: Discussionmentioning
confidence: 97%
“…We have also not detected PMQR genes in any of the isolates. Other resistance mechanisms not tested in this study such as multidrug efflux pumps, other PMQR mechanisms recently described in Salmonella such as oqxAB efflux pump [19], and altered outer membrane porins might be involved [14]. …”
Section: Discussionmentioning
confidence: 99%
“…These resistance determinants have been observed in various gram negative organisms including Salmonella [16, 17]. In recent years, the rate of resistance to ciprofloxacin has increased considerably in both clinical and food isolates of Salmonella [6, 18, 19]. …”
Section: Introductionmentioning
confidence: 99%
“…Mutations at different sites contribute to different levels of resistance to ciprofloxacin, and simultaneous mutations in both gyrA and parC genes produce high levels of ciprofloxacin resistance. Besides, most isolates with decreased susceptibility to ciprofloxacin contain a mutation in gyrA or PMQR genes (Ling et al, 2003; Lin et al, 2015). In the present study, we found that six isolates had double mutations (S83F/D87N or D87G) in the gyrA gene and a single mutation (S80R) in the parC gene.…”
Section: Discussionmentioning
confidence: 99%